1999
DOI: 10.1046/j.1365-2249.1999.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Spleen autotransplantation provides restoration of functional splenic lymphoid compartments and improves the humoral immune response to pneumococcal polysaccharide vaccine

Abstract: After splenectomy, patients have an increased risk of overwhelming post-splenectomy infection (OPSI) or sepsis involving encapsulated bacteria such as pneumococcus. The value of spleen autotransplantation after splenectomy because of trauma has long been questioned. Much attention has been given to the restoration of mononuclear phagocyte system (MPS) function, which appeared to be similar to that of splenectomized individuals. The presence of specific anti-pneumococcal antibodies may enhance phagocytosis of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
16

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 30 publications
3
32
0
16
Order By: Relevance
“…However, it has to be stressed that the ability of such patients to produce antipolysaccharide antibodies that are involved in humoral defense against encapsulated bacteria and are synthesized by a splenic B-lymphocyte subpopulation has still to be evaluated. 24,25 Obvious clinical benefits could be documented in patients with HS after subtotal splenectomy. In our experience, chronic discomfort that does not correlate with the intensity of anemia is a frequent finding in untreated patients with HS.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has to be stressed that the ability of such patients to produce antipolysaccharide antibodies that are involved in humoral defense against encapsulated bacteria and are synthesized by a splenic B-lymphocyte subpopulation has still to be evaluated. 24,25 Obvious clinical benefits could be documented in patients with HS after subtotal splenectomy. In our experience, chronic discomfort that does not correlate with the intensity of anemia is a frequent finding in untreated patients with HS.…”
Section: Discussionmentioning
confidence: 99%
“…We used a rat model for which it was previously shown that splenectomy had a clearly negative effect on the antipolysaccharide antibody response (21). Because PCV contain only a limited number (4 to 11) of pneumococcal serotypes compared with the number contained by 23-valent PPS vaccines, we studied the potential benefit of admixture of additional polysaccharides with the PCV.…”
mentioning
confidence: 99%
“…Hence, autotransplantation or maintenance of residual splenic tissue is now standard practice [91]. Vaccinations against encapsulated organisms are administered to manage these two cohorts showing physical and/or functional impairment of the splenic marginal zone, however, the use of conjugate vaccines (where available) in these cases appears to be more justified than that of polysaccharide antigens.…”
Section: Discussionmentioning
confidence: 99%